1987
DOI: 10.1111/j.1365-2621.1987.tb14044.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an alkaline proteinase and exopeptidase from shrimp (Penaeus indicus) muscle

Abstract: Activities of an alkaline proteinase and an exopeptidase were detected in the muscle of shrimp. Both enzymes could be extracted with unbuffered 0.5% KCI. The shrimp muscle alkaline proteinase, optimally active at pH 8.0 and 6O"C, was partially purified and characterized. The heat stable enzyme had an apparent molecular weight of 250 KDa. Protein substrates such as casein, azocasein, azocoll and hemoglobin were hydrolyzed by the enzyme while it showed no action on bovine serum albumin and the synthetic substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…2a). Doke and Ninjoor (1987) have also reported the presence of an alkaline metal dependent serine protease, with activity at pH 7 in shrimp ( Penaeus indicus ).…”
Section: Resultsmentioning
confidence: 95%
“…2a). Doke and Ninjoor (1987) have also reported the presence of an alkaline metal dependent serine protease, with activity at pH 7 in shrimp ( Penaeus indicus ).…”
Section: Resultsmentioning
confidence: 95%
“…2000). The B. subtilis JM‐3 protease did not hydrolyze BTEE, which was the specific substrate for chymotrypsin‐like proteases (Doke and Ninojoor 1987; Choi et al. 1999b).…”
Section: Resultsmentioning
confidence: 99%
“…2005). The B. subtilis JM‐3 protease was not inhibited by 1‐mM NEM and PCMB, which were specific inhibitors for cysteine proteases (Doke and Ninojoor 1987), and by EDTA, which was the specific inhibitor for metalloproteases (Oliveria et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) were alkaline proteases. Previously Doke and Ninjoor (1987) reported that cathepsin B, H and alkaline proteases in shrimp muscle hydrolyzed casein, hemoglobin and benzoyal-Arg-β-napthalamide. Ezquerra et al (1999) reported Leu-, Gly-, Ala-, Val-, Met-, Pro-and Arg-amonipeptidase activities of extracts of white shrimp hepatopancreas.…”
Section: Resultsmentioning
confidence: 99%